1984
DOI: 10.1111/j.2164-4918.1984.tb00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Where Have All the Women Writers Gone?

Abstract: Women are underrepresented as writers, especially as senior authors, and on editorial boards of professional journals, including those of the AACD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1989
1989
1990
1990

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(30 reference statements)
0
0
1
Order By: Relevance
“…Boice and Johnson (1984) similarly found that gender was not related either to writing output or to most writing habits. However, these findings contradict those cited in other research (see Boice & Jones, 1984;Over, 1982b;and White, 1984) where greater productivity is reported for the men. Over (1982b) reported that women psychologists were more likely to be perfectionist writers -which is perhaps related to our finding that women appeared to be 'thinkers' rather than 'doers'.…”
Section: Sex and Age Differencescontrasting
confidence: 99%
“…Boice and Johnson (1984) similarly found that gender was not related either to writing output or to most writing habits. However, these findings contradict those cited in other research (see Boice & Jones, 1984;Over, 1982b;and White, 1984) where greater productivity is reported for the men. Over (1982b) reported that women psychologists were more likely to be perfectionist writers -which is perhaps related to our finding that women appeared to be 'thinkers' rather than 'doers'.…”
Section: Sex and Age Differencescontrasting
confidence: 99%